Rogue gunslinger & Hunting down the horseman - Daniels, B. J. (Harlequin intrigue., 2018)
Rogue Gunslinger- Bestselling author TJ Clementine thought she<U+2019>d be safe with her sisters during the holiday. She was wrong. Now her “biggest fan” has followed TJ to Whitehorse. The only person who can help TJ is ruggedly handsome loner Silas Walker<U+2014>if she can trust him. Hunting Down the Horseman- Brave and single, Jud Corbett loves the life he leads outside his hometown of Whitehorse. Then he meets Faith Bailey<U+2026>a local woman who<U+2019>s had too many “accidents” of late. Jud can<U+2019>t help but be a hero, but will he still be a bachelor after his encounter with Faith?